Significance of intramammary lymph node in multimodality imaging - Boregowdanapalya, Anitha (International Journal of Research in Medical Sciences, 2025)
The internal mammary lymphatic system, alongside the axillary lymphatic system, is a key pathway for lymphatic drainage from the breast and a significant route for metastatic spread in breast cancer. Internal mammary lymph node (IMLN) involvement is associated with poor prognosis, regardless of axillary lymph node status. Intramammary lymph nodes (IMLNs), often benign incidental findings, require accurate differentiation between normal and abnormal features to guide appropriate diagnostic and therapeutic measures. Multimodality imaging, including mammography, ultrasound, MRI, and PET-CT, is essential for characterizing IMLNs, offering complementary insights into morphology and function. Accurate evaluation of IMLNs aids in breast cancer staging, with the American Joint Committee on Cancer (AJCC) incorporating their status into staging systems, reflecting their prognostic importance. Emerging technologies, such as radiomics and artificial intelligence (AI), promise to enhance diagnostic precision, potentially reducing invasive procedures. This review highlights the clinical significance of IMLNs and the pivotal role of imaging in their evaluation.